2021
DOI: 10.1177/0885328221997998
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic capability of strontium and icariin-loaded TiO2 nanotube coatings in vitro and in osteoporotic rats

Abstract: Titanium (Ti) and Ti alloys are widely used biomaterials, but they lack osteogenic capability for rapid bone integration. To improve osseointegration of Ti implants, TiO2 nanotubes were prepared using the anodizing oxidation technique, and strontium (Sr) combined with icariin (ICA) was loaded on TiO2 nanotube coatings. Cell adhesion and proliferation of MC3T3-E1 cells, alkaline phosphatase (ALP) activity, mineralization of extracellular matrix, and bone formation around titanium implants in ovariectomized rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A possible explanation may be that these nanostructures, mainly TNT80, allowed macrophages to overcome the surface spatial limitations, leading to a higher number of filopodia and implicitly to an enhanced cell adhesion. For instance, this increase in cell attachment was reported to activate actin stress fibres (RhoA)/Rho-associated protein kinase (ROCK) signalling pathway, inducing macrophage activation and sequentially their switch towards a M2 phenotype [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation may be that these nanostructures, mainly TNT80, allowed macrophages to overcome the surface spatial limitations, leading to a higher number of filopodia and implicitly to an enhanced cell adhesion. For instance, this increase in cell attachment was reported to activate actin stress fibres (RhoA)/Rho-associated protein kinase (ROCK) signalling pathway, inducing macrophage activation and sequentially their switch towards a M2 phenotype [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…TiO2 nanotubes produced by anodizing and loaded with Sr combined with icariin (ICA) showed a better effect on cell adhesion, proliferation and higher mineralization activity than pure Ti and TiO2 coatings. Furthermore, in osteoporotic rats, more bone was formed around the implants loaded with Sr and ICA [207]. Similarly, Y-doped TiO2 coatings on Ti6Al4V produced by PEO demonstrated good biocompatibility on osteoblastic precursor cells and fibroblast cells with increasing doping concentration of yttrium and excellent antibacterial activity against E. coli and S. aureus [208].…”
Section: Oxidesmentioning
confidence: 90%
“…For instance, Zhu et al loaded ICA on the TNTs and confirmed that ICA-loaded TNTs could accelerate osseointegration via enhancing ECM mineralization and new bone formation. These effects were more remarkable after joining Sr [ 162 ]. Furthermore, the addition of composite coating optimized the local drug delivery system.…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%